Enrolment in the first stage of early childhood education and students’ academic performance: a cross-country analysis. - López-Agudo, Luis Alejandro; Marcenaro-Gutiérrez, Óscar David (Taylor & Francis, 2024)
Parents have the option of enrolling their children in the first stage of early childhood education (from 0 to 3 years of age). However, not all parents decide to do so, waiting until the second stage of early childhood education to enrol them in the education system (from 3 to 5 years of age), or even until compulsory education when their children are around 6. We intend to analyse the influence of students’ enrolment in the first stage of early childhood education on their fourth-grade reading scores. This analysis has been performed using data from the Progress in International Reading Literacy Study (PIRLS) 2011 and 2016 for 39 countries and an instrumental variable approach to go beyond simple correlation. We find that attending the first stage of early childhood education has a positive influence on students’ reading scores in 18 countries, whereas it presents a null influence in 16 countries.
School Effectiveness and School Improvement
Keywords: Educación - Modelos matemáticos; Enseñanza preescolar; Rendimiento académico; Lectura; First stage of early childhood education; Instrumental variables; Fourth grade; Reading